Pengaruh E-Commerce Knowledge , Risiko, Dan Teknologi Terhadap Kepercayaan Dan Niat Beli Online - Suciana, Sanda Kharoma; , Dr. Anton Agus Setyawan, SE, M.Si; , Drs. Wiyadi, M.M., Ph.D (2017)
This research aims to identify and analyze: 1) Ecommerce knowledge, risk and technology to trust satisfaction. 2. Perceived technology to purchase intention satisfaction 3. Trust of purchase intention. The data of the research is the premier data which was obtained from from the answers of 148 respondents with incidental sampling method. This research is using Struktural Equation Model (SEM). The test results concluded that all of variable instrument are valid and reliable as the tool of data collector. The result of data analysis obtained that : 1. Ecommece knowledge has not the positive and significant impact to trust. 2. Perception of risk has the positive and significant impact on trust 3. Perception of technology has not positive and significant impact to trust. 4. Perception of technology has the positive and significant impact bought intention. 5. Purchase intention has the positive and significant impact trust.